Noninvasive Uterine Electromyography For Prediction of Preterm Delivery - UCOVNIK, Miha L (2010)
OBJECTIVE: Power spectrum (PS) of uterine electromyography (EMG) can identify true labor. EMG propagation velocity (PV) to diagnose labor has not been reported. The objective was to compare uterine EMG against current methods to predict preterm delivery. STUDY DESIGN: EMG was recorded in 116 patients (preterm labor, n=20; preterm non-labor, n=68; term labor, n=22; term non-labor, n=6). Student’s t-test was used to compare EMG values for labor vs. non-labor (P<0.05 significant). Predictive values of EMG, Bishop-score, contractions on tocogram, and transvaginal cervical length were calculated using receiver-operator-characteristics analysis. RESULTS: PV was higher in preterm and term labor compared with non-labor (P<0.001). Combined PV and PS peak frequency predicted preterm delivery within 7 days with area-under-the-curve (AUC) = 0.96. Bishop score, contractions, and cervical length had AUC of 0.72, 0.67, and 0.54. CONCLUSIONS: Uterine EMG PV and PS peak frequency more accurately identify true preterm labor than clinical methods.